Comparação do padrão citológico de incidentalomas em relação a nódulos tireoidianos clinicamente relevantes - Silva, Larissa Francelina (2018)
Introduction: The clinical spectrum of thyroid nodules vary from an incidental and asymptomatic nodule, in which cancer is the major concern, to clinically relevant nodules (≥ 1 cm) with compressive symptoms. This study aims to compare clinical, ultrasonographic and cytological features of thyroid incidentalomas with Materials and Methods: This cross-sectional retrospective study included 812 patients with thyroid nodules, who underwent thyroid ultrasonography and Fine Needle Aspiration from January 2007 to December 2013. We collected clinical and sonographic characteristics, and cytology was expressed according to the Bethesda classification. Results: Of the 812 patients, 32.1% presented incidentalomas (< 165 cm). Thyroid incidentalomas presented as solid hypoechogenic and with peripheral vascularization lesions, while nodules ≥ 1 cm were mixed, hyperechogenic, with central and peripheral vascularization. Bethesda I class was most commonly found among incidentalomas, and Bethesda II in the clinically relevant nodules’ group. The frequency of malignant cytologies (Bethesda V and VI) was low in both groups. Conclusion: Despite the ultrasound characteristics found in thyroid incidentalomas, they did not present a higher frequency of suspicious or malignant cytologies. Instead, insufficient results were more frequent in this group, which reinforces the current tendency to value suspicious sonographic characteristics altogether and consider the possibility of follow-up of subcentimetric nodules.